Effects of Nitrogenous Fertilizers on Seed Germination of Orobanche solmsii C.D. Clarke - Bista, Anjana (Ecoprint: An International Journal of Ecology, 2015)
Seven nutrient chemicals were tested in vitro during pre- and post- conditioning period in order to know their effects on O. solmsii seed germination. All the concentrations (4, 8 and 16 mM) of nutrient applied during pre-conditioning period inhibited germination, whereas the effects of chemicals applied during post-conditioning period was either inhibitory or ineffective depending upon the nutrients. Ammonium nitrate and ammonium chloride was effective in reducing seed germination by 43% and 41%, respectively, and were more than any other ammonium salts. This study showed that all forms of nitrogen are not equally effective in reducing of germination. ECOPRINT 21: 73-78, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11907